(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article is devoted to the study of the structural and functional features of the thymus. The main function of the formation of subpopulations of T-lymphocytes is the thymus, due to the intertissue and intercellular relationships of microenvironment cells, which have their own structural and functional features.